Effects of Femtocell Ultradense Deployment on Downlink Performance in LTE Heterogeneous Networks - Al-Omari M.S.; Alomari M.A.; Ramli A.R.; Sali A.; Azmir R.S.; Yusoff M.H. (Hindawi Limited, 2023)
Heterogeneous networks; Quality of service; Urban planning; Wireless networks; Data bandwidth; Downlink performance; Femtocells; High quality service; Indoor environment; LTE heterogeneous networks; Macro cells; Service Quality; Ultradense; Wireless devices; Femtocell